(untitled) (Contemporary Journal of Social Science Review, 2025)
This research analyzes the subversion of patriarchal descriptive structures through the contrasting representations of women in Eugene O’Neill’s Mourning Becomes Electra and Arthur Miller’s The Crucible and.Drawing on Simone de Beauvoir’s famous work The Second Sex, the research examines how representative female characters face, discuss and resist their living experiences within patriarchal societal frameworks. The female characters like Christine Mannon and Abigail Williams, synchronized with the femme fatale prototype, undermine male-dominated social structure through their moral transgressions and sexual activity. Likewise, Lavinia Mannon and Elizabeth Proctor are placed inside the cultural draft of the honorable, inactive woman. Both disclose moments of confrontation and independence that confuse their assigned roles. Utilizing deep textual analysis supported by a data-driven approach—tracking dialogue sharing, activity in plot development, and thematic reappearance—the research paper discloses how both American plays challenge gendered power associations. Through Beauvoir’s critical lens, the female characters are interrogated as subjects striving to exceed their roles as “Other,” presenting ethical and narrative power within stories that historically marginalize them. The current research debates that both plays, though emerging from respected historical and dramatic traditions, offer a critical room in which female characters` voices disturb the masculine structures that attempt to contain them.